CONTRIBUTION OF EDUCATIONAL MANAGEMENT IN IMPROVING THE EFFECTIVENESS OF ISLAMIC EDUCATIONAL INSTITUTIONS - Kurniasari, Putri; Wahidi, M. Iqbal; Habib, Syafaatul; Khrisfison (International Journal of Multidisciplinary Reseach, 2025)
Educational management is a systematic effort in managing various resources to achieve educational goals efficiently and effectively. In the context of Islamic educational institutions, the quality of management greatly influences the success of the educational process, including the planning, implementation, supervision, and evaluation stages of the program. This study aims to examine the extent to which educational management contributes to increasing the effectiveness of Islamic educational institutions. The method used is a qualitative approach with library research techniques, namely analyzing various relevant references. The findings show that the application of appropriate educational management principles can increase the effectiveness of institutions, both in terms of administration, learning processes, and human resource development. Systematic management also helps create a productive, collaborative, and quality-oriented learning environment. Thus, strengthening educational management is a key element in building superior and competitive Islamic educational institutions.